2017
DOI: 10.1002/dmrr.2927
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome response to short‐term dietary interventions in reactive hypoglycemia subjects

Abstract: The Ma-Pi 2 diet, with its high fibre load, was effective in increasing the production of SCFAs by the gut microbiota. Because these metabolites are known for their ability to counterbalance the metabolic deregulation in persons with glucose impairment disorders, their increased bioavailability could be of some relevance in reactive hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…Additional research has shown minimal changes in the gut microbiome following exercise, although not under the context of severe metabolic syndrome (Kern et al, 2020 ; Taniguchi et al, 2018 ). The data presented herein substantiate the notion that dietary factors such as those associated with a “Western diet” have a significant impact on the gut microbiome (Cignarella et al, 2018 ; Quercia et al, 2017 ). Nevertheless, given that animals are consuming identical diets, this raises the possibility that a secreted factor(s) is able to traverse the intestinal barrier and impact specific bacterial species, a hypothesis under current investigation (Barger et al, 2020 ; Dalton et al, 2019 ; de Sire et al, 2018 ).…”
Section: Discussionsupporting
confidence: 82%
“…Additional research has shown minimal changes in the gut microbiome following exercise, although not under the context of severe metabolic syndrome (Kern et al, 2020 ; Taniguchi et al, 2018 ). The data presented herein substantiate the notion that dietary factors such as those associated with a “Western diet” have a significant impact on the gut microbiome (Cignarella et al, 2018 ; Quercia et al, 2017 ). Nevertheless, given that animals are consuming identical diets, this raises the possibility that a secreted factor(s) is able to traverse the intestinal barrier and impact specific bacterial species, a hypothesis under current investigation (Barger et al, 2020 ; Dalton et al, 2019 ; de Sire et al, 2018 ).…”
Section: Discussionsupporting
confidence: 82%
“…There is an interrelated link between nutrition and the microbiota because dietary habits influence colonization and life-long microbiome rearrangement. A pilot study involving patients with RH evaluated the composition of the gut microbiota and the potential role of a diet rich in fiber and fermented products [ 42 ]. The short-term observation confirmed the positive impact of diet composition on the increase in short-chain fatty acids (SCFAs), which are end products of the microbiota fermentation of complex carbohydrates in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…The Ma-Pi 2 diet is rich in seaweeds, wholegrains, legumes and fermented products. Both diets followed for 3 days in 12 reactive hypoglycemic participants, induced no changes in the gut microbial composition, however the SCFA's in the Ma-Pi 2 diet group was increased significantly from baseline to the 4th day (99).…”
Section: Mediterranean Diet and Gut Microbiotamentioning
confidence: 97%